Faktor-Faktor yang Berhubungan dengan Pernikahan Usia Dini di Kabupaten Purworejo Jawa Tengah - Rafidah Ova Emilia, Budi Wahyuni (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Early marriage  is  common  in  developing countries  including  Indonesia. Factors  related  to  early marriage  are,  among  others;  education,  economic,  and  social  aspects. The  impacts  of  early marriage  are dropout and  teenage pregnancy which causes  rejection  to  pregnancy.  In District of Purworejo marriage  below 20 years  of age  is still  as much  as  20.6%  (Community Health  and Nutrition Research Laboratory  2005).Objective: The  study aimed  to  identify  factors  related  to early marriage.Method: This was  an  observational  study with  cross  sectional design  using  both  qualitative and  quantitative approaches. Data were  obtained  through  questionnaires  and  interview  guide. Samples  of  the  study were  90 married women, who were  systematically  chosen,  respondents  of  longitudinal  surveillance  of Community Health and Nutrition Research Laboratory, 90 parents of  the  respondent, 1  religious  leader,  2 community  leaders and  1 staff  of office  of Religious Affairs. Hypothetical  test used  chi square with p<0.05, CI 95%. Multivariable analysis  used  logistic  regression.Results:  Low  perception about marriage  showed  the most  related  to  the  decision  for  early marriage. Other factors  related  to  early marriage were  low  level of  education  (RP=2.90, CI 95%=1.30–6.49,  p=0.000),  low  familyeconomic  status  (RP=1.75, CI 95%=1.05  – 2.91   p=0.017). Unemployed  parents  (RP=1.48, CI95%=0.88-2.49 p=0.23)  and  parents’  low  perception  about marriage  (RP=1.5, CI95%=0.96-2.37  p=0.05) were  not  strongly related with  early marriage.Conclusion:  Factors  related  to early marriage were  perception of  respondents about marriage, education  of respondents,  family  economic status,  and unemployed  parents.Keywords:  early marriage,  perception  about marriage,  family  economic status,  education